2015
DOI: 10.1111/1751-2980.12262
|View full text |Cite
|
Sign up to set email alerts
|

Overlap of gastroesophageal reflux disease and functional bowel disorders in the general Chinese rural population

Abstract: GERD-FBD overlap is more common than expected by chance in the general rural population, and anxiety is significantly related to the overlap.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 21 publications
1
8
0
Order By: Relevance
“…When studies were pooled according to the method of administration of the questionnaire, again there were significant differences in prevalence between individual studies. When the Rome III questionnaire was administered at an interview in 29 studies, 20,22,23,31,[33][34][35]37,[39][40][41][42][45][46][47][48][49][51][52][53]60,61,[65][66][67]69,70,75,79 the prevalence of IBS ranged from 0.4% in India and Ghana, 79 to 20.9% in Singapore, 61 with a pooled prevalence of 5.9% (95% CI 4.6% to 7.4%). When the same questionnaire was self-completed in 22 studies 24,28-30,32,36,38,43,44,50,54,56,58,59,62-64,68,71,77-79 the prevalence ranged from 2.0% in the USA, 58 to 29.2% in Croatia, 24 with a pooled prevalence of 12.0% (95% CI 9.6% to 14.6%).…”
Section: Administrationmentioning
confidence: 99%
“…When studies were pooled according to the method of administration of the questionnaire, again there were significant differences in prevalence between individual studies. When the Rome III questionnaire was administered at an interview in 29 studies, 20,22,23,31,[33][34][35]37,[39][40][41][42][45][46][47][48][49][51][52][53]60,61,[65][66][67]69,70,75,79 the prevalence of IBS ranged from 0.4% in India and Ghana, 79 to 20.9% in Singapore, 61 with a pooled prevalence of 5.9% (95% CI 4.6% to 7.4%). When the same questionnaire was self-completed in 22 studies 24,28-30,32,36,38,43,44,50,54,56,58,59,62-64,68,71,77-79 the prevalence ranged from 2.0% in the USA, 58 to 29.2% in Croatia, 24 with a pooled prevalence of 12.0% (95% CI 9.6% to 14.6%).…”
Section: Administrationmentioning
confidence: 99%
“…Sixty-nine studies reported the duration of symptoms required to meet criteria for gastro-oesophageal reflux, with 36 using 12 months,11 24 28 29 31 32 35–37 41 42 46–48 56 62 65 67 69 70 73 74 77 79–83 86 94 100 102 104 107 111 115 6 using 6 months,19 34 38 51 71 101 11 using 3 months,23 26 33 39 40 43 44 52 60 87 109 7 using 1 month53 64 78 88 92 106 118 and 9 using 1 week 27 59 66 84 99 105 112 114 117. The prevalence of gastro-oesophageal reflux symptoms was highest in studies that used a 1-month timeframe (20.1%), but was also higher in studies that used 6 months, compared with those that used 12 months (17.6% vs 14.1%) (table 2).…”
Section: Resultsmentioning
confidence: 99%
“…In the remaining studies, 30 used a postal questionnaire,19–23 25–27 29 32 36 37 39 54 56 60–62 64 66 69 75 78 81 94 97 100 106 111 118 22 conducted a face-to-face interview,11 31 33 41 45 53 58 59 63 65 67 70 71 76 91 95 99 101 103 107 115 117 16 used a self-completed questionnaire (including internet-based questionnaires),24 35 44 48 50 77 84 85 87–90 96 110 112 114 17 used an interview-administered questionnaire28 30 38 51 55 57 73 80 82 83 86 92 98 102 104 116 119 and 16 used a questionnaire completed during a telephone interview 34 40 42 43 46 47 49 52 68 72 74 79 93 105 108 109. Pooled prevalence of gastro-oesophageal reflux symptoms was highest in the 30 studies that used a postal q...…”
Section: Resultsmentioning
confidence: 99%
“…The prevalence of symptom‐based GERD (symptoms of heartburn or acid regurgitation occurring at least once per week) is between 0.8% and 26.5%, but mostly between 4% and 10% (Table ) . The prevalence was low in studies carried out in the 1990s–early 2000s and has increased in studies done after 2010.…”
Section: Changing Trends and Current Status Of Gerd In East Asiamentioning
confidence: 99%
“…[11][12][13] The prevalence of symptom-based GERD (symptoms of heartburn or acid regurgitation occurring at least once per week) is between 0.8% and 26.5%, but mostly between 4% and 10% ( Table 1). [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] The prevalence was low in studies carried out in the 1990s-early 2000s and has increased in studies done after 2010. Geographically, GERD prevalence has been generally higher in Japan compared to the other Eastern countries.…”
Section: Introductionmentioning
confidence: 99%